(untitled) (International Journal of Engineering and Computer Science, 2018)
In today’s world there is a great need for the design of low power and area efficient high performance DSP system.FIR filter is considered to be the fundamental device in the broad application of wireless as well as the video and image processing system. With the aim of getting the reliable operation, these filters are protected using the Error correction Code. Filters are broadly used in dealing out with signal processing and communication systems. As the complexity of communications and signal processing systems increases, so does the number of blocks or elements that they have. In many cases, some of those elements operate in parallel performing the same processing on different signals. In this paper, the idea of applying coding techniques to protect parallel filters is addressed in a more general way. In particular, it is shown that the fact that filter inputs and outputs are not bits but numbers enables a more efficient protection. This reduces the protection overhead and makes the number of redundant filters independent of the number of parallel filters. The proposed scheme is first described and then illustrated with two case studies. Finally, both the effectiveness in protecting against errors and the cost are evaluated for an FPGA implementation.